2017
DOI: 10.1017/s0007485317000207
|View full text |Cite
|
Sign up to set email alerts
|

Feeding performance and life table parameters of Khapra Beetle,Trogoderma granariumEverts (Coleoptera: Dermestidae) on various barley cultivars

Abstract: The Khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae), is a common pest of cereal grains and other stored products. In this study, the effects of ten barley cultivars (Abidar, Bahman, Line20, Line22, Line30, Lisuei, Lokht11, Makuyi, Sahand, and Sahraa) were evaluated on life table parameters and nutritional indices of T. granarium under the following laboratory conditions: 33 ± 1°C, 60 ± 5% RH, and a photoperiod of 14: 10 (L: D) h. Life history parameters of T. granarium could be appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…There are complex interactions of macronutrients with other dietary characteristics influencing lifespan and reproduction rate (Coskun et al, 2005; Chen et al, 2009). Primary plant metabolites, including nitrogen, protein, and carbohydrates have been shown to strongly affect the feeding and growth of insect herbivores (Soufbaf et al, 2012; Golizadeh and Abedi, 2017); however, less attention has been given to secondary plant metabolites and their effects on insect performance (Harvey, 2005; Ode, 2006; Mardani-Talaee et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are complex interactions of macronutrients with other dietary characteristics influencing lifespan and reproduction rate (Coskun et al, 2005; Chen et al, 2009). Primary plant metabolites, including nitrogen, protein, and carbohydrates have been shown to strongly affect the feeding and growth of insect herbivores (Soufbaf et al, 2012; Golizadeh and Abedi, 2017); however, less attention has been given to secondary plant metabolites and their effects on insect performance (Harvey, 2005; Ode, 2006; Mardani-Talaee et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Host plant resistance to insects can also be manipulated using chemical elicitation of secondary metabolites, which can confer resistance to insects (War et al, 2012). Proper use of resistant cultivars in pest management strategies requires knowledge of life table parameters and biological variables of pests (Nawrot et al, 2010; Golizadeh and Abedi, 2017; Gvozdenac et al, 2018; Karimi-Pormehr et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that the various cultivars of grains influence development, longevity and reproductive variables of stored-product pests ( Chougourou et al 2013 , Borzoui and Naseri 2016 , Naseri and Borzoui 2016 , Golizadeh and Abedi 2017 ). The results of present study suggest that R. dominica fed on the 12 barley cultivars tested is able to complete its development period and reproduction at the different rates.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been suggested that an integrated pest management strategy to protect grains in storage systems could be performed utilizing resistant cultivars ( Rossa et al 2013 , Hosseininejad and Naseri 2015 , Golizadeh and Abedi 2017 , Majd-Marani et al 2017 ). However, there is a little published information that has examined the management of R. dominica by resistant cultivars.…”
mentioning
confidence: 99%
“…The recorded values of the intrinsic and finite rate of increase were lower than the corresponding ones of other stored-product insects, indicating that T. castaneum had a lower population increase potential even on semolina. For example, the khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae) exhibited 2.50-4.21, 2.79-5.51 or 3.36-4.71 times higher values of intrinsic rate of increase and 1.02-1.05, 1.03-1.07 or 1.04-1.05 when fed on different varieties of barley, hybrids of maize or grain commodities, respectively [16,40,41]. Rahimi Namin et al [33] reported shorter durations of development of larvae, shorter longevities of female or male adults and higher values of the intrinsic or finite rate of increase when T. castaneum fed on different varieties of barley than the observed corresponding values of the current study on semolina.…”
Section: Discussionmentioning
confidence: 99%